Dokumentowanie dna zbiorników wodnych terenów zabytkowych - Czochański, Marian; Kośka, Tadeusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1984)
Inland waters to be found on geodetically documented historical sites are usually represented in the form of shore-line contours sometimes supplemented by quotation of the water level in the day of measurement. The authors, however, draw attention to the fact that cartographically pictured bottom of such water reservoirs may provide plentiful and valuable information for archaeologists allowing to compile more conclusions and a correct interpretation of "visible" landscape elements. It may also be useful in designing projects of protection, exposition, restauration or development of a historical site. On the example of the early-mediaeval city – Kiszewski Castle, Stara Kiszewa district in Gdansk Province, the authors are discussing problems connected with field surveying operations and present variants of cartographic–studies in the form of cross-section of hydrometrie superimposed sections and contour plans of the bottom in the examined water reservoirs on this archaeological position.